Estructura Factorial, Confiabilidad y Validez de Contenido de la Escala LASSIHS en Estudiantes de Educación Secundaria - Ernst Jourdan, Cindy Anali (2023)
The present study aimed to examine the factorial structure, reliability and content validity of the LASSI-HS scale in Argentine secondary education students. The study included 496 students from 11 to 19 years old (M= 14.56; SD= 1.80), of both sexes, who completed the LASSI-HS scale. Aiken's V coefficient (.97) provided evidence of the instrument´s content validity. The confirmatory factor analysis offered support for the threefactor structure that was interpreted following Olivares and Tallent´s (1994) model: i.e., (1) affective / effortrelated activities, (2) cognitive activities, and (3) anxiety-arousing activities. The internal consistency of the adapted instrument was satisfactory both for the general scale and for each of the dimensions. The results suggest that the LASSI-HS shows satisfactory psychometric properties and represents a valid and reliable measure to assess learning strategies in adolescents without a clinical diagnosis.